Marktstrategien der Kurienbanken Die Geschäfte der Alberti, Medici und Spinelli in Deutschland (1400-1475) - Weissen, Kurt (Heidelberg University Publishing (heiUP), 2021)
With their branch networks and partners, the Florentine banks dominated international monetary transactions of the 15th century. Thanks to their presence in the main commercial centres of the continent, the merchant bankers from Tuscany dominated the cashless processing of large transfers of money from all over Europe to the Roman Curia. Kurt Weissen examines how curia bankers, such as the Alberti and the Medici, connected Germany to this payment system via Bruges and Venice. He analyses the role played by the establishment of branches in Lübeck, Cologne, Basel and Constance and the importance of cooperation with German merchant companies.